Preparation of multiresponsive hydrophilic molecularly imprinted microspheres for rapid separation of gardenia yellow and geniposide from gardenia fruit. (16th April 2022) - Wang, Jinshuang; Ye, Qin; Yu, Ningxiang; Huan, Weiwei; Sun, Jingliang; Nie, Xiaohua; Meng, Xianghe
Highlight: Multi-responsive hydrophilic molecularly imprinted microspheres (HMIMs) were prepared. HMIMs show pH/thermo-controlled uptake/release of gardenia yellow and magnetic separation. SPE process for gardenia yellow from water extract use HMIMs as sorbent was optimized. Gardenia yellow and geniposide were separated successfully by the developed approach. Abstract: In this work, a robust method for the separation of gardenia yellow and geniposide from gardenia fruit was developed based on a molecularly imprinted solid phase extraction (MISPE) procedure. First, hydrophilic molecularly imprinted microspheres (HMIMs) were prepared using gardenia yellow as the template via reversible addition fragmentation chain transfer (RAFT) precipitation polymerization. The resultant HMIMs demonstrated the multiresponsiveness to pH, temperature, and magnetism, achieving controllable uptake and release of gardenia yellow and easy recovery by external magnets. Meanwhile, the HMIMs possessed high adsorption capacity, fast binding kinetics, specific recognition, and reusability. Finally, a MISPE approach using HMIMs as adsorbent was developed for extraction of gardenia yellow and purification of geniposide after optimization of the adsorption and elution conditions. Thus, efficient separation of gardenia yellow and geniposide with relative purities of 99.77 ± 0.05% (94.04 ± 0.10% recovered) and 94.50 ± 0.62% (95.40 ± 0.86% recovered), respectively, was achieved.